For what values of x is f(x)=(x-3)(x+2)(x-1)f(x)=(x3)(x+2)(x1) concave or convex?

1 Answer
May 27, 2018

Refer Explanation.

Explanation:

Given that: f(x) =(x-3)(x+2)(x-1)f(x)=(x3)(x+2)(x1)
:. f(x) =(x^2-x-6)(x-1)
:. f(x) =(x^3-x^2-6x-x^2+x+6)
:. f(x) =(x^3-2x^2-5x+6)

By using second derivative test,

  1. For the function to be concave downward:f''(x)<0
    f(x) =(x^3-2x^2-5x+6)
    f'(x) =3x^2-4x-5
    f''(x) =6x-4
    For the function to be concave downward:
    f''(x)<0
    :.6x-4<0
    :.3x-2<0
    :. color(blue)(x<2/3)

  2. For the function to be concave upward:f''(x)>0
    f(x) =(x^3-2x^2-5x+6)
    f'(x) =3x^2-4x-5
    f''(x) =6x-4
    For the function to be concave upward:
    f''(x)>0
    :.6x-4>0
    :.3x-2>0
    :. color(blue)(x>2/3)